Respuesta :
Answer:
q-0
p-3
Step-by-step explanation:
there are two ways to solve elimination or substitution method I'll use the latter
so take the second equation and find an expression equal to p
p-2q=3
p=2q+3
substitute the above expression in the first equation
(2q+3)1+2q=3
open brackets
2q+3+2q=3
collect like terms
4q+3=3
solve
4q=0
q=0
substitute q in any equation you want I'll choose the second
p-(2×0)=3
p-0=3
p=3
Answer:
p = 3 ; q = 0
Step-by-step explanation:
In this linear pair of eqn. in 2 variables , they have a unique solution i.e. they will have only single solution . We know that
[tex]p + 2q=3[/tex] & also [tex]p -2q=3[/tex] . So, we can also equate them as :-
[tex]p + 2q = p-2q[/tex] (∵ Both the eqn. have 3 in their right hand side product )
Solving the eqn. gives,
[tex]=> 2q + 2q = p-p\\=> 4q=0\\=>q=0[/tex]
Putting the value of q in any one of the linear eqn gives ,
[tex]p+2q=3\\=> p+2(0)=3\\=>p+0=3\\=>p=3[/tex]